A Metal-Free Approach to Carboxylic Acids by Oxidation of Alkyl, Aryl, or Heteroaryl Alkyl Ketones or Arylalkynes - Aravinda Kumar, K. A.; Venkateswarlu, Vunnam; Vishwakarma, Ram A.; Sawant, Sanghapal D. (Synthesis, 2015)
The metal-free oxidation of dialkyl, alkyl aryl, or alkyl heteroaryl ketones or arylalkynes to the corresponding carboxylic acids is achieved using an oxidative mixture of Oxone and trifluoroacetic acid. This green method is a simple and mild protocol to obtain carboxylic derivatives in excellent yields.
Keywords: ketones; alkynes; oxidation; carboxylic acids; green chemistry